Structural Changes to Immune Organs in Rats after Intermittent Fasting Following a High Carb and Fat Diet - Ika Fidianingsih ,; Titis Nurmasitoh ,; Aulia Dian Ashari ,; Desi Yana ,; Dwi Nur Ahsani, (Journal of Pharmacy and Nutrition Sciences, 2018)
Background:A diet high in carbs and fat puts people at risk of obesity. Obesity causes changes in the immune system and increases the risk of premature ageing, including in the lymphoid organs ― such as the thymus and spleen. Fasting is expected to improve the immune system. The purpose of this research is to determine the effects of intermittent fasting on images of the structure of the thymus, the number of fat cells, Hassall’s corpuscles of the thymus, the area and density of pulp white spleen, and the number of leukocytes in Wistar rats (Rattus norvegicus) fed a diet high in carbs and fat. Methods:An experimental study with post-test only control group design, with 15 male rat subjects aged 2.5 months were divided into three groups: first group had a diet that was ad libitum (AL); second group were given a diet high in fats and carbohydrates for 1 month then were fed ad libitum (HCL); and third group were given a diet high in fat and carbohydrates for 1 month continued with alternating 12 hour fasting periods for 72 days (F). Results: Total Hassall’s corpuscles of AL, HCL, and F groups were 1.33 ± 077; 2.58 ± 1.35; and 0.69 ± 0.27, respectively(p = 0.008). Fat cells were not found in the thymus. The largest white pulp in the spleen was found in group F, followed by AL, while the smallest was found in group of HCL (p = 0.01). The most depleted white pulp density was the HCL group. There is no significant difference in the number of leukocytes and different leukocyte count between the groups (p> 0.05). Conclusion: Intermittent fasting for 72 days affects the number of Hassall’s corpuscles in the thymus and the width of white pulp in the spleen of Wistar rats.